EVALUATION OF ACCUMULATED HEAVY METALS IN SOIL AND PLANT BODIES OF Oryza sativa L. and Triticum vulgare L. - Katepogu, Raju; Varada, Vishnuvardhan; Middepogu, Ayya Raju; T, Damodhraram (Innoriginal: International Journal of Sciences, 2016)
The Rice and Wheat crops are very important edible species in India, which were also stable food for diet of all the human beings. The main objective of the work is to evaluate the accumulated heavy metal levels in soil and plant bodies through pot culture experiments. The experiments were conducted by in-vitro condition in the department laboratory. The effluents samples were collected the karakambadi and renigunta industrial areas, Andhra Pradesh, India. It has been observed that the crop plant parts were affected by the effluents which were impacted on shoot, stem and root of rice and wheat crop plant parts. The statistical values of plant samples have significantly reduced when compared with control. In this study, water crop plants were subjected to higher doses of lead and cadmium, leads to significantly declined in the growth. The results suggests that water crops are not affected by oxidative stress, in spite of the presence of higher dose of lead and cadmium in the hydroponic medium, as would be anticipated for a species that has efficiently survived in a highly polluted environment.Â 